On the new Afrotropical genus Suffrica with discovery of an abdominal gland and a dual femoral organ (Araneae, Zodariidae) - Henrard, Arnaud; Jocqué, Rudy (Zootaxa, 2015)
A new genus, Suffrica, is described from Tanzania and Kenya. It contains three new species occurring in the Eastern Arc Mountains and the adjacent Mkomazi Game Reserve: S. exotica, S. chawia and S. gus. They are characterized by a remarkable combination of features which has not been documented in spiders so far: a pair of femoral organs on each leg, a gland on the dorsal side of the abdomen in both sexes and a dorsal abdominal groove in males. A dual femoral organ appears to occur in species of the genus Suffasia Jocqué, 1991 and Asceua Thorell, 1887. The discovery of a new African genus close to Suffasia is remarkable since the latter genus is known only from Asia.